An Emerging Integrated Middle-Range Theory on Asian Women's Leadership in Nursing. (July 2018) - Im, Eun-Ok; Broome, Marion E.; Inouye, Jillian; Kunaviktikul, Wipada; Oh, Eui Geum; Sakashita, Reiko; Yi, Myungsun; Huang, Lian-Hua; Tsai, Hsiu-Min; Wang, Hsiu-Hung
Introduction: Asian cultures reflect patriarchal cultural values and attitudes, which likely have influenced women leaders in their countries differently from women in Western cultures. However, virtually no leadership theories have been developed to reflect the experiences and development of nursing leaders from Asian cultures. The purpose of this article is to present an emerging integrated middle-range theory on Asian women's leadership in nursing.Methodology: Using an integrative approach, the theory was developed based on three major sources: the leadership frames of Bolman and Deal, literature reviews, and exemplars/cases from five different countries.Results: The theory includes two main domains (leadership frames and leadership contexts). The domain of leadership frames includes human resources/networks, structure/organization, national/international politics, and symbols. The domain of leadership contexts includes cultural contexts, sociopolitical contexts, and gendered contexts.Discussion: This theory will help understand nursing leadership in Asian cultures and provide directions for future nurse leaders in this ever-changing globalized world.